2019
DOI: 10.1111/vsu.13281
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in 40 cats with discrete intermediate‐ or large‐cell gastrointestinal lymphoma masses treated with surgical mass resection (2005‐2015)

Abstract: Objective To report outcomes in cats with discrete intermediate‐ and large‐cell gastrointestinal (GI) lymphoma masses after surgical resection. Study design Retrospective clinical case series. Animals Forty client‐owned cats in which intermediate‐ or large‐cell GI lymphoma was diagnosed. Methods Records of 40 cats in which discrete intermediate‐ or large‐cell GI lymphoma masses were diagnosed between 2005 and 2015 were reviewed. Cats were included if they survived curative intent surgery and had a known outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 14 publications
(64 reference statements)
0
9
2
5
Order By: Relevance
“…However, we consider that aggressive resection of discrete GI lymphoma well-localized in the stomach may be a reasonable consideration, even if the GI lymphoma is expected as high-grade lymphoma. The two latest studies reported that feline discrete intermediate-or large-cell GI lymphoma with complete surgical margins may survive longer than with incomplete margin or without surgical lymphoma masses resection [4,20]. Probably, complete surgical margins in this case contribute to have good prognosis.…”
mentioning
confidence: 78%
“…However, we consider that aggressive resection of discrete GI lymphoma well-localized in the stomach may be a reasonable consideration, even if the GI lymphoma is expected as high-grade lymphoma. The two latest studies reported that feline discrete intermediate-or large-cell GI lymphoma with complete surgical margins may survive longer than with incomplete margin or without surgical lymphoma masses resection [4,20]. Probably, complete surgical margins in this case contribute to have good prognosis.…”
mentioning
confidence: 78%
“…Disease progression was considered to have occurred in cats with recurrence of clinical signs whether or not repeat imaging was available. This method of reporting is commonly seen in feline intestinal tumor literature (22)(23)(24), although this method may have overrepresented the number of cats with progressive disease in the current study. The authors elected to not perform a multivariate analysis due to the limited number of cats with complete data sets, which could have resulted in a model with unreliable conclusions and a lack of generalizability.…”
Section: Discussionmentioning
confidence: 99%
“…25 Other studies have found no prognostic information on clinical staging of cats with alimentary lymphoma. 26,27 For cats with intestinal MCT and intestinal adenocarcinoma, the absence of LN metastasis is associated with a better prognosis. 28–30…”
Section: Discussionmentioning
confidence: 99%